Preoperative assessment of splenic involvement in patients with peritoneal carcinomatosis with CT and MR imaging. Issue 110 (January 2019) - Berthelin, Marie-Anne; Barral, Matthias; Eveno, Clarisse; Rousset, Pascal; Dautry, Raphaël; Pocard, Marc; Soyer, Philippe; Dohan, Anthony
Abstract: Purpose: To estimate the performances of computed tomography (CT) and magnetic resonance imaging (MRI) and those of the combination of CT with MRI in the identification of splenic involvement in patients with peritoneal carcinomatosis (PC). Material and method: CT and MRI examinations of 26 patients with PC with splenic involvement and 26 patients with PC and no splenic involvement treated by total cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) were reviewed. There were 32 women and 20 men with a mean age of 53.44 ± 12.22 (SD) years (range: 20–73 years). Imaging examinations were reviewed separately as three independent imaging sets (CT only, MRI only and CT with MRI) by two independent readers. A consensus was reached during a joint reading session and these results were used for determining the performances of the three imaging sets in the diagnosis of splenic involvement using surgical and histopathological findings as standard of reference. Results: Splenic involvement was histologically proven in 26/52 patients (50%). There were no significant differences in sensitivity, specificity and accuracy for the diagnosis of splenic involvement between CT, MRI and CT + MRI, with respectively 84.62%, 96.15% and 90.00% for CT, 84.62%, 84.62% and 85.00% for MRI and 92.31%, 92.31% and 92.00% for CT + MRI. Conclusion: CT and MRI have similar sensitivities, specificites and accuracies for the diagnosis of splenic involvement in patients with PC. The combination of CT and MRI does not significantly improve the preoperative diagnosis of splenic involvement in patients with PC compared to CT only.